Structure of abdominal injury and its consequences - Gogiya, Madona (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2021)
Introduction. Mechanical injuries are a leading cause of disability and premature death among the working-age population in most countries worldwide. Injuries to the abdominal and retroperitoneal organs (abdominal trauma) significantly aggravate the course of trauma and are a frequent cause of death. The aim of the study was to analyse the structure and outcome of the treatment of abdominal trauma victims. Materials and methods. On the basis of the polytrauma department of the municipal non-profit enterprise «Municipal clinical hospital of emergency and urgent medical care named after A. I. Meshchaninov» of Kharkiv City Council councilаnalysis damage structure and the results of treatment of 240 patients with abdominal trauma were carried out, the main causes of lethal outcomes were determined. Results. Most of the patients with abdominal trauma were male (78,7%), and they were young (18 to 44 years old) (72,5 %). The cause of injury in 95 (39.6 %) victims was road traffic accident, in 58 (24.2 %) – catatrauma; in 65 (27.1 %) – domestic injury. In the abdominal cavity, parenchymatous organs (spleen and/or liver) were injured most frequently, identified in 66.7 % of victims. In 26.3 % of patients revealed damage to the small or large intestine, in some cases, trauma to the stomach and gallbladder was detected. In 37 (15.4 %), mesenteric injury was detected, and in 32 (13.3 %), omental injury was detected. Among retroperitoneal organs the renal trauma was frequent – 46 (19.2 %), pancreatic and urinary bladder injuries were revealed in 27 (11.2%) and in 13 (5.4%) cases, retroperitoneal haematoma was revealed in 63 (26.7 % ) victims. In 178 (74.2 %) victims a combined trauma was diagnosed: thoracic in 129 (53.8%) cases, skeletal in 96 (40 %), craniocerebral in 84 (35 %). Combined injuries of one anatomofunctional region were diagnosed in 80 (33.3 %), two in 67 (27.9 %), and three in 31 (12.9 %) victims. During in-hospital treatment, 34 (14.2 %) victims died, of which 12 (35 %) during the first week after injury. The duration of inpatient treatment for the victims who were discharged was 15.0 [12.0; 25.0] beds/day. The causes of mortality and prolonged hospitalization (more than 14 days) in most cases were cardiovascular, respiratory, purulent-septic and renal complications. Conclusion. Abdominal parenchymal injuries predominate in the structure of abdominal trauma, occurring in 66.7 % of victims. Combined (thoracic, skeletal and/or craniocerebral) trauma occurs in 74.2 % of victims. The fatality rate for isolated abdominal trauma was 4.8 %, with a significant increase in cases of combined trauma, up to 41.9 % for combined thoracic, skeletal and craniocerebral trauma.